Effects of continuous fertilization on bioavailability and fractionation of cadmium in soil and its uptake by rice (Oryza sativa L.). (1st June 2018) - Huang, Qingqing; Yu, Yao; Wan, Yanan; Wang, Qi; Luo, Zhang; Qiao, Yuhui; Su, Dechun; Li, Huafen
Abstract: A four-year field trial was conducted in a rice paddy in southern China to determine the effects of continuous phosphate fertilizer, pig manure, chicken manure, and sewage sludge application on soil Cd accumulation in soil and Cd uptake by rice. The results showed that continuous application of fertilizers with higher Cd levels caused Cd to accumulate and redistribute in various soil fractions. In turn, these effects influenced Cd bioavailability in rice plants. After four years of phosphate fertilizer, pig manure, chicken manure, and sewage sludge application, the annual soil Cd accumulation rates were 0.007–0.032 mg kg −1, 0.005–0.022 mg kg −1, 0.002–0.013 mg kg −1, and 0.032–0.087 mg kg −1, respectively. Relative to the control, the pig- and chicken manure treatments significantly increased soil pH and reduced DTPA-extractable Cd (DTPA-Cd) and the exchangeable Cd fraction (Exc-Cd). In contrast, sewage sludge application significantly increased DTPA-Cd and Cd in all soil fractions. Phosphate fertilization had no significant effect on soil pH, DTPA-Cd, or Exc-Cd. Pearson's correlation coefficients showed that the rice grain Cd levels varied directly with DTPA-Cd, and Exc-Cd but inversely with soil pH. Pig- or chicken manure decreased rice grain Cd content, but sewage sludge increased both soil Cd availability and rice grain Cd uptake. Application of phosphate fertilizer had no significant effect on rice grain Cd content. The continuous use of organic- or phosphate fertilizer with elevated Cd content at high application rates may induce soil Cd accumulation and influence rice grain Cd accumulation. Graphical abstract: Image 1 Highlights: Continuous application of various fertilizers with high Cd levels caused Cd accumulation in soil. Phosphate fertilizer had no significant effect on Cd bioavailability or its accumulation in rice grain. Livestock manure decreased soil Cd bioavailability and reduced Cd accumulation in rice grain. Sewage sludge significantly increased soil Cd bioavailability and rice grain Cd content.